Pedagogical necessity of developing methodological training of future primary school teachers - Abdiyeva , Koysintosh; Nomurodova , Khurshidakhon (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The article examines the fundamental changes in all areas of our lives today, including new methodologies in preschool and primary education, the role of models, the role of 4K skills in the training of future primary school teachers, and the problems of modern education. Future primary school teachers should develop creativity in their native language and reading literacy, which is manifested in thinking, communication, emotions, and a specific type of activity.